Study of the dynamic fracture effect using slotted cartridge decoupling charge blasting. (July 2017) - Wang, Yanbing
Abstract: The explosion loading testing system of digital laser dynamic caustics was performed to analyze the dynamic fracture effect of blasting detonation crack of different charge structures, and to examine the directional fracture-controlled blasting mechanism of slotted cartridge. The explicit dynamics analysis code LS-DYNA was used to simulate the slotted cartridge blasting and the generation of initial crack, and the relation between decoupling coefficient and blasting damage was also investigated. The finding shows that when the decoupling coefficient α1 equals 1.67, the fracture effect of slotted cartridge is optimal; the propagation velocity and the dynamic stress intensity factor of the detonation primary crack show a downward trend with oscillation, and reach a smaller peak in the middle and late stage of crack propagation; the plasticine medium as the buffer between the explosion product and the walls of borehole transfers energy well. The dynamic energy release rate values of the secondary crack as a whole is less than that of two primary cracks. When the decoupling coefficient is smaller than 1.67, the gas pressure, accelerated speed and velocity peak on the point of borehole walls in the slotted direction parallel to the detonation point will rapidly decrease with the increase of decoupling coefficient, but when the decoupling coefficient is greater than 1.67, these parameters will slowly decrease with the increase of decoupling coefficient. Highlights: Use new DLDC system. Simulate the phenomenon by LS-DYNA. Discuss the relation between decoupling coefficient and blasting damage.